PENGARUH UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA - Muhammad Farhan Genio Srikandi; Hesty Ervianni Zulaecha; Imam Hidayat; Imas Kismanah (Akuntansi, 2022)
This study investigated size effect to earnings management. In this study, it is investigated whether medium and large-sized firm more aggressive to use earnings management through reporting positive earnings to avoid losses and/or earnings decreases by examining the earnings (change) frequency distribution and probit analysis. Docu-mented is empirical evidence that small-, medium- and large-sized firms tend to report positive earnings to avoid earnings losses. However, this study observed that firm size plays differing roles in earnings management. This study found that medium-and large-sized firms do not engage more earnings management aggressively than small firms for both avoiding reporting earnings losses and earnings decreases.